Comparison of methods for determining parameters related to ankle joint quasi-stiffness during quiet standing - Kaylie Lau; Kai Lon Fok; Jonguk Lee; Kei Masani (PLoS ONE, 2026)
Ankle joint quasi-stiffness is a measure representing the control of quiet standing. Here we investigated three methods for determining parameters associated with ankle joint quasi-stiffness. Eleven healthy, young males were asked to stand quietly with eyes open (EO) and eyes closed (EC). Ankle joint quasi-stiffness was computed using two methods, one proposed by Winter et al. (Winter DA, et al. J Neurophysiol 80: 1211−1221, 1998) ( K q s 1 ) and another by Loram and Lakie (Loram ID, et al. J Physiol 540: 1111−1124, 2002) ( K q s 2 ). Both values were normalized using participants’ body sizes. The short-term scaling exponent in stabilogram diffusion analysis ( H s ), which has been linked to quasi-stiffness, was applied. A two-way repeated measures ANOVA revealed a significant main effect of methodology (p < 0.0001, partial η² = 0.42), but no significant effect of eye condition (p = 0.1947, partial η² = 0.06), nor interaction effect (p = 0.4742, partial η² = 0.02). Intraclass Correlation Coefficient (ICC(3,1)) analysis indicates good reliability between K q s 1 and K q s 2 with an ICC value of 0.858 (p < 0.001) in the EO condition, and moderate reliability with an ICC value of 0.718 (p = 0.004) in the EC condition. H s and K q s 1 exhibited a very strong negative correlation in the EO ( ρ = −0.909) condition and a moderately strong negative correlation in the EC ( ρ = −0.782) condition. H s and K q s 2 exhibited moderately strong negative correlation in both the EO ( ρ = −0.664) and EC ( ρ = −0.555) conditions. The good and moderate reliability between K q s 1 and K q s 2 suggests that both measures capture similar stiffness attributes relating to their neuro-mechanical components, despite a significant methodological difference. Additionally, relatively high correlations of H s with K q s 1 and with K q s 2 suggest that the stochastic characteristics of centre of pressure in the short period indeed reflect the overall quasi-stiffness at the ankle joint.